2014
DOI: 10.1039/c3cc48231f
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric ion-gels containing an amino acid ionic liquid for facilitated CO2transport media

Abstract: Novel ion-gel films containing an amino acid ionic liquid were fabricated by free radical polymerization of vinyl monomers. These high strength materials demonstrated superior CO2 permeability and separation performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…80 wt% AAIL contents did not break under compression stress of more than 25 MPa (Fig. S6(a), ESI †), which is more than 25 Ɵmes higher than those previously reported for [P 4444 ][Pro]-based ion gels consisting of PVP and PDMAAm single networks prepared by our group 8 . During compression, no AAIL leakage from the gel network was observed as a consequence of good compatibility between PDMAAm and the AAILs.…”
Section: Amino Acid Ionic Liquid-based Tough Ion Gel Membrane For Co mentioning
confidence: 52%
See 2 more Smart Citations
“…80 wt% AAIL contents did not break under compression stress of more than 25 MPa (Fig. S6(a), ESI †), which is more than 25 Ɵmes higher than those previously reported for [P 4444 ][Pro]-based ion gels consisting of PVP and PDMAAm single networks prepared by our group 8 . During compression, no AAIL leakage from the gel network was observed as a consequence of good compatibility between PDMAAm and the AAILs.…”
Section: Amino Acid Ionic Liquid-based Tough Ion Gel Membrane For Co mentioning
confidence: 52%
“…For the fabrication of AAIL-based DN gels, the most important parameter is the compatibility between AAILs and the polymer networks. In a previous report, 8 we found that polyvinylpyrrolidone (PVP) and polydimethylacrylamide (PDMAAm) have good compatibility with several phosphonium-based AAILs. Because PVP and PDMAAm are neutral polymers, we adopted them as the second network of the AAIL-based DN ion gels.…”
Section: Amino Acid Ionic Liquid-based Tough Ion Gel Membrane For Co mentioning
confidence: 96%
See 1 more Smart Citation
“…The same research group mentioned that there is a little difference in the CO 2 solubility among the AAILs with a common trihexhyltetradecylphosphonium cation [15]. Because of the excellent CO 2 solubility, the AAILs were applied not only to absorbents but also as components for adsorbents and separation membranes [16][17][18][19]…”
Section: Ionic Liquids (Ilsmentioning
confidence: 99%
“…

and the use of low-molecular-weight gelators and oligomeric electrolyte gelators. [2][3][4][5][6][7] In practical applications, the high mechanical strength of ion gels is an indispensable property of this soft material. [2][3][4][5][6][7] In practical applications, the high mechanical strength of ion gels is an indispensable property of this soft material.

…”
mentioning
confidence: 99%